Floral Biology and pollination requirements of sesame (Sesamum indicum L.) - Patrícia Barreto de Andrade; Breno Magalhães Freitas; Epifânica Emanuela de Macêdo Rocha; José Antônio de Lima; Leonardo Lopes Rufino (Acta Scientiarum. Animal Sciences, 2014)
This study aimed to investigate the floral biology and pollination requirements of sesame (Sesamum indicum L.), cultivar CNPA G2. The study was carried out at Barbalha, State of Ceará, and consisted of two phases: floral biology and pollination requirements. Flowers were observed as for time of anthesis, lifespan and stigma receptivity, and were applied the following pollination treatments: open pollination, hand cross-pollination, hand self-pollination, pollination restricted with tulle bags and pollination restricted with paper bags. Significant differences (p < 0.05) were detected between treatments for the number of fruits harvested 30 days after pollination. It was shown that the sesame plant presents a mixed-pollination system, because it can produce fruit whatever the type of pollination tested. Flowers are able to autopollinate and do not depend on external agents. Pollinations restricted with paper and tulle bags produced fruit with greater number of heavier seeds. It is concluded that sesame crop is able to autopollinate and benefit from both self-pollination and cross-pollination.